UTICAJ PLIMORFIZMA b2 ADRENERGIČNOG RECEPTORA (RS1042713 I RS1042714) NA ANTROPOMETERIJSKI, HORMONSKI I LIPIDNI PROFIL SINDROMA POLICISTIČNIH OVARIJA - Daghestani, Maha H.; Omair, Maha; Daghestani, Mazin; Abdel-Razeq, Sonya S.; Kaya, Namik; Warsy, Arjumand (Journal of Medical Biochemistry, 2020)
Background: Polycystic ovarian syndrome (PCOS) is a frequently encountered disorder. This study aimed to identify polymorphisms in ADRB2 in Saudi PCOS development and to study its influence on lipids, hormones, and anthropometric parameters.Methods: Saudi females (100) suffering from PCOS and healthy controls (100) were investigated. The estimation of cholesterol, triglycerides, high-density lipoprotein (HDL-C), low-density lipoprotein (LDL-C), plasma glucose, leptin, insulin, and ghrelin were carried out. The DNA was extracted, and ADRB2 fragment carrying the exon 1 was amplified and sequenced. Results: The waist, W/H ratio, lipids, glucose, and insulin were significantly higher in the obese PCOS compared to the normal weight group. The leptin and ghrelin were not different. Two single nucleotide polymorphisms (SNPs): rs1042713(Arg16Gly; A>G) and rs1042714 (Gln27Glu; C>G) were identified. The genotype and allele frequency of rs1042713 did not differ in the total PCOS and normal weight, and obese PCOS compare to the controls. However, rs1042714 was significantly associated with PCOS development, where the minor G allele was protective against PCOS development. Conclusions: The rs1042714 polymorphism of the ADRB associates with PCOS development in Saudis, while rs1042713 does not. However, the GG genotype of rs1042713 associates significantly with elevated BMI, waist, hip, W/H, and leptin, and decreased ghrelin. On the other hand, rs1042714 genotypes do not associate with any abnormality except the homozygous GG have higher triglycerides and lower HDL-C. Interestingly, glucose showed different correlation patterns in individuals carrying different genotypes of the two studied SNP, indicating clearly that the metabolic responses to a normal nutrient are significantly influenced by the genotypes of the SNPs in ADRB2.